The Influence of Learning Management System on the Success of Blended Learning : Systematic Literature Review - Putra, I Made Dharma; Parwati, Ni Nyoman; Agustini, Ketut; Putra, Anak Agung Adi Wiryya (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to examine the effect of Learning Management System (LMS) on the success of blended learning using the Systematic Literature Review (SLR) method. The literature analyzed came from accredited journals indexed in Scopus and Google Scholar databases, with a publication range of 2020-2024 and the selection process was carried out based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) so that 20 journals were obtained that showed that LMS is effective in increasing the success of blended learning. Based on the analysis of articles and journals, this review highlights that LMS significantly increases several aspects of blended learning. Specifically, the use of LMS leads to a significant increase in several aspects of blended learning. LMS has been shown to be a critical determinant in enhancing student engagement within blended learning environments. Furthermore, LMS supports early data detection, which ultimately improves student learning outcomes. Students also experience higher satisfaction levels when LMS is integrated into blended learning courses. Beyond student benefits, LMS facilitates enhanced course management and delivery, providing a robust framework for modern education with effective organization and flexible learning experiences. The effectiveness of teaching is also improved through the integration of technology-mediated learning approaches via LMS. Moreover, LMS can accelerate the adaptation of teachers to distance education, increasing adoption rates and supporting various aspects of blended learning implementation. From this study, it can be seen that in general it shows indicators that LMS can improve student learning outcomes and learning independence in accordance with the objectives of blended learning. However, the effectiveness of LMS varies by educational context, and the intention to continue using LMS is influenced by perceptions of usefulness and satisfaction. The review concludes that several key elements maximize the impact of LMS on blended learning success: positive user experience, active teacher involvement, utilization of LMS data, and consideration of the educational context. LMS adoption is driven by the need for flexibility and to accelerate the digitalization of education, its can be seen from the increased effectiveness and ease of learning with flexible and cost-effective access to materials, as well as increasing learning independence by facilitating students to learn according to their respective speeds and learning styles.Effective implementation, however, requires addressing teacher anxiety by providing adequate support, such as internet and computer/gadget availability. These findings confirm that LMS plays a very important role in increasing the success of blended.